(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the long-term outcomes regarding urinary and sexual functions, cosmetic perception, and reproductive psychology in adult males undergoing surgical correction for hypospadias using the transverse pedicled preputial island flap technique. Subjects and methods: A cross-sectional descriptive study was conducted on 18 adult patients with a history of hypospadias who underwent urethral reconstruction using a transverse preputial flap. Assessment tools included the penile perception score (PPS) and the international index of erectile function (IIEF-5). Results: The overall satisfaction rate regarding penile morphology reached 88.8% (including 66.6% satisfied and 22.2% very satisfied); only 11.2% expressed dissatisfaction due to retracting scar tissue or residual curvature. The vast majority of patients exhibited normal erectile function, with only 1 case (5.6%) presenting with moderate erectile dysfunction. Conclusion: Urethroplasty using a transverse preputial flap yields favorable and stable long-term outcomes in both urinary and sexual functions for most patients. The comprehensive success of the surgery should be evaluated based on both anatomical restoration and the patient-reported quality of life. Future studies with larger sample sizes and longer follow-up periods are required for the most objective assessment.